Leptin activates cytosolic calcium responses through protein kinase-C dependent mechanism in immortalized RFamide-related peptide-3 neurons - Ozcan, Mete; Saatci, Tugrul; Ayar, Ahmet; Canpolat, Sinan; Kelestimur, Haluk (Elsevier Science Bv, 2015)
RFamide-related peptide-3 (RFRP-3), a mammalian ortholog of avian gonad tropin-inhibitory hormone (GnIH), seems to be an important regulator of the hypothalamus-pituitary-gonadal (HPG) reproductive axis. Leptin, a permissive hormonal regulator of fertility, provides energy signal to brain. According to current view, leptin does not act directly on gonadotrophin-releasing hormone (GnRH) neurons. RFRP-3 neurons have been shown to express leptin receptors. The goal of the present study was to examine whether leptin acts through RFRP-3 neurons to modulate activity of the GnRH neurons. For this aim, the effects of leptin on intracellular free Ca2+ levels ([Ca2+](i)) in RFRP-3 neurons were investigated by using in vitro calcium imaging system. In the present study, rHypoE-7 cell line was used as a model to explore the effects of leptin on RFRP-3 neurons. rHypoE-7 cells were placed on glass coverslip and loaded with 1 mu M Fura-2 AM. [Ca2+](i) responses were quantified by the changes in 340/380 ratio. Leptin (0.1-10 mu M) caused increases in [Ca2+](i) in a dose-dependent manner. The changes in [Ca2+](i) were significantly attenuated by pretreatment with protein kinase C inhibitor. These results demonstrate that leptin activates intracellular calcium signaling in RFRP-3 neurons through PKC-dependent pathway, and thus leptin may exert its effect on GnRH neurons by means of RFRP-3 cells. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Leptin; RFamide-related peptide-3 neurons; Calcium signaling; Protein ldnase-C